2006
DOI: 10.1177/039139880602901208
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Angiogenesis in Tissue Engineering: Developing Multicellular Matrices with Multiple Capacities

Abstract: One of the aims of tissue engineering is to be able to develop multi-tissue organs in the future. This requires the optimization of conditions for the differentiation of multiple cell types and maintenance of the differentiated phenotype within complex engineered tissues. The goal of this study was to develop prototype tissue engineered matrices to support the simultaneous growth of different cell types with a particular focus on the angiogenic process. We examined two different matrix compositions for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In a micropig lamellar keratoplasty model, TERP-5 constructs (without supporting or surrounding collagen-CS elements) showed complete reepithelialization within 1 wk, new nerve ingrowth, and epithelial and anterior stromal morphologies (including a regenerated basement membrane) which were comparable to allografts; within 21 d, touch sensitivity had returned to preoperative levels, indicating the restoration of neural function. In an interesting additional application of the TERP material, TERP was blended with fibrinogen, and growth factors to support angiogenesis, and was seeded with isolated DRGs and human umbilical vein endothelial cells (HUVECs), to form a scleral model; this was molded into a ring and the center was filled with a keratocyte-seeded collagen-CS corneal equivalent, with epithelial cells seeded on top (55). In vitro, this appeared to be a good scleral model, as HUVECs led to angiogenesis within the sclera, but the vasculature did not penetrate into the corneal regions; however, nerves originating from the DRGs extended through the sclera and into the corneal stroma and epithelial layers with normal morphologies.…”
Section: Advances In Tissue-engineered Corneal Equivalentsmentioning
confidence: 99%
“…In a micropig lamellar keratoplasty model, TERP-5 constructs (without supporting or surrounding collagen-CS elements) showed complete reepithelialization within 1 wk, new nerve ingrowth, and epithelial and anterior stromal morphologies (including a regenerated basement membrane) which were comparable to allografts; within 21 d, touch sensitivity had returned to preoperative levels, indicating the restoration of neural function. In an interesting additional application of the TERP material, TERP was blended with fibrinogen, and growth factors to support angiogenesis, and was seeded with isolated DRGs and human umbilical vein endothelial cells (HUVECs), to form a scleral model; this was molded into a ring and the center was filled with a keratocyte-seeded collagen-CS corneal equivalent, with epithelial cells seeded on top (55). In vitro, this appeared to be a good scleral model, as HUVECs led to angiogenesis within the sclera, but the vasculature did not penetrate into the corneal regions; however, nerves originating from the DRGs extended through the sclera and into the corneal stroma and epithelial layers with normal morphologies.…”
Section: Advances In Tissue-engineered Corneal Equivalentsmentioning
confidence: 99%
“…Previous work, including our own, has shown that tissue engineered collagen-based matrices can support multiple tissues and cell types, 12,13 and constitute suitable cell delivery vehicles. [13][14][15] It has been hypothesized that the collagen, which mimics the extracellular matrix, may provide local physical retention and a good platform for cell seeding during direct cell transplantation.…”
Section: Clinical Perspective See P 204mentioning
confidence: 90%
“…[13][14][15] It has been hypothesized that the collagen, which mimics the extracellular matrix, may provide local physical retention and a good platform for cell seeding during direct cell transplantation. 14 However, the evaluation of the ability of matrices to improve cell viability and engraftment has so far been limited primarily to histological assessment of tissue at a single time point.…”
Section: Clinical Perspective See P 204mentioning
confidence: 99%
“…They have been widely used in the last decade for a variety of tissue engineering applications in adipose [21], cardiovascular [22,23], ocular [24,25], muscle [26,27], liver [28,29], skin [30,31], cartilage [32,33], and bone [34,35] tissues. Moreover, fibrin hydrogels are able to promote angiogenesis [36,37].…”
Section: Fibrinmentioning
confidence: 99%